1975
DOI: 10.1097/00000658-197502000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Human Tissue Reaction to Sutures

Abstract: Tissue reaction to sutures was studied in 666 specimens obtained from patients from one day to 23 years after operation. Reaction to catgut depends on the stage of absorption and is mainly histocytic in type. Nonabsorbable sutures are encapsulated by a rim of connective tissue, while near the suture histocytes, giant cells and lymphocytes are found. This is most marked with silk and cotton, less so with Dacron, and least with nylon and wire. Tissue infiltration into the suture interstics is variable. The react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(31 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…Apart from limitations of animal experiments, these foreign body reactions appear quite similar to those seen in humans [13,28]. Considering our expectation that a CTI reflects tension and the fact that we placed the suture without any mechanical strain, we were surprised by the fact that all sutures still showed a pronounced bilateral CTI.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Apart from limitations of animal experiments, these foreign body reactions appear quite similar to those seen in humans [13,28]. Considering our expectation that a CTI reflects tension and the fact that we placed the suture without any mechanical strain, we were surprised by the fact that all sutures still showed a pronounced bilateral CTI.…”
Section: Discussionmentioning
confidence: 72%
“…In the majority of these studies tension was applied to the suture [9,10,11,12]. However, Postlethwaite et al [13 ]already noted acellular fibrous tissue on the side of the suture toward the tension; while opposite to the direction of tension there resulted a cellular infiltrate marking the path of the migrating and thus cutting action. In a study of Hoer et al, this was confirmed, and because of the characteristic shape, it was named ‘comet tail phenomenon’ [14].…”
Section: Introductionmentioning
confidence: 99%
“…Peak inflammatory response is seen between second and seventh day with abundance of polymorphonuclear leukocytes, lymphocytes, and large monocytes in dermis. [3] Between the third and eighth day, the epithelial cells deeply invade the suture tracts.…”
Section: Basic Characteristics Of Wound Healing After Basic Charactermentioning
confidence: 99%
“…It passes through the tissue more easily but knot security is inferior. Absorption of Glycomer 631 [3,4] is complete between 90 and 110 days.…”
Section: Glycomer 631mentioning
confidence: 99%
“…5,6 The numerous options for wound closure are well described in the plastic and dermatological surgery literature and include suture, staples, adhesive tapes and glues. 4,39,40,45 A review of the orthopaedic literature for calcaneal fractures, tibial plafond fractures, and fracture-dislocations of the ankle reveals that nylon suture is the most common choice to close the skin. 14,27,44,46 Basic science investigations evaluating the characteristics of closure materials generally support the use of nylon suture or staples.…”
Section: Wound Closure Materialsmentioning
confidence: 99%